Narrativas da dor no espaço da devoção: A performance na via sacra de Monte Santo (BA) - Costa, Neffertite Marques da (2024)
This thesis defined its formal object of research around the way of cross of Monte Santo, Bahia, which began to be built in 1785, by the Capuchin missionary Apolônio de Todi. Conceived as an instrument of devotion, the religious intervention in this region of the countryside of Bahia transported to the ancient Serra do Piquaraçá the proposal of the sacred mounts, present in the European continent, inspired by Mount Calvary, where Jesus would have been crucified, according to the texts of the Gospels. With a total of twenty-five chapels, on a path that goes around the mountain, the Capuchin friars undertaking, which continues to this day, has the specificity of, in addition to the narrative of the Passion of Christ, through the stations of the way of cross, having added to the devotional body the narrative of Mary's sorrows, in the cult of Our Lady of Sorrows, and devotion to the Souls in Purgatory. This study presents the dynamics of ruptures and permanences of devotional practices in Monte Santo over time, considering the relations between the Catholic Church, the constituted governments, the religious brotherhoods, the blessed and the devotees, in order to point out, in the context of local memory, a confrontation between what has been called "narratives of pain". In addition to the different narratives produced about Monte Santo, the dense description was used, according to the methodology discussed by Geertz, for the interpretation of devotional practices, recorded during the fieldwork carried out during Holy Week, in the years 2022 and 2023, and in All Saint’s Day, in 2022, based on the concept of performance, according to Turner, Schechner and Taylor, to produce a narrative about the processions of the Way of the Cross, the Meeting and the Dead Christ. In this way, the thesis offers an understanding of the religious universe of the countryside, understanding the various devotional practices around Holy Week and the All Saint’s Day, in Monte Santo, as scenes of a performance, which composes a system of learning, storage and transmission of knowledge, according to Taylor's formulation, in which the devotees relive and update the sufferings of Jesus Christ and Our Lady, transforming their own pains into acceptance and hope that reanimate the journey of their lives